Communication—An Extension of Gitlow's Methodology for Designing Abortion Clinics - Kleijnen, J. P. C. (Management Science, 1979)
Comments about Gitlow, H. S. 1976. A methodology for determining the optimal design of a free standing abortion clinic. Management Sci. 22 (12, August) 1289–1298.